УДОСКОНАЛЕННЯ АПАРАТУРИ ДЛЯ ЕЛЕКТРОФІЗІОЛОГІЧНИХ ДОСЛІДЖЕНЬ РОСЛИННИХ БІООБ'ЄКТІВ - Никифорова , Л.Є.; Кізім , І.В.; Богатирьов , Ю.О. (Інститут електродинаміки НАН України, Київ, 2012)
Certain requirement to the apparatus of research vital functions of vegetable bioobjects. A chart over of device is brought for measuring of bioelectric potentials and his principle of action is described. The worked out device allows to conduct continuous registration of metabolic difference bioelectric potentials with determination of peak extremums negative and positive semiwave. References 3, figure 1.